Design of two-stage force amplification frame for piezoelectric energy harvester / Teoh Choe-Yung ... [et al.] - Teoh, Choe-Yung; Wong, Joon Kit; Ko, Ying Hao; Abdul Hamid, Muhammad Najib; Ooi, Lu Ean; Tan, Wei Hong (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
This paper describes the design of a two-stage force amplification frame for the piezoelectric energy harvester to capture mechanical energy from walking human footsteps. The frame design optimises the stress distribution to improve the force amplification ratio on the existing footstep energy harvesters. The magnification of the input force exerted on a piezoelectric stack increases the system's power output. A combination of single and compound two-stage frame design with additional linkage support was proposed, which maximise the conversion of tension to compression forces. The proposed frame also significantly reduces the maximum displacement of the frame to ensure walking comfort. The frame is tested with the input force of 85 N to 120 N based on the adult footstep during walking and running. The simulated results show that the proposed frame has a force amplification ratio of 25.3, an 11.85% improvement from the existing frames.